Effects of phytoplankton community composition and productivity on sea surface pCO2 variations in the Southern Ocean. (June 2020) - Takao, Shintaro; Nakaoka, Shin-Ichiro; Hashihama, Fuminori; Shimada, Keishi; Yoshikawa-Inoue, Hisayuki; Hirawake, Toru; Kanda, Jota; Hashida, Gen; Suzuki, Koji
Abstract: The Southern Ocean is a vast net sink for atmospheric carbon dioxide (CO2 ), with marine phytoplankton playing a crucial role in CO2 fixation. We assessed how changes in the dominant phytoplankton community and net primary productivity (NPP) affected variations in the partial pressure of CO2 in surface water ( p CO2 sw ) in the Indian sector of the Southern Ocean during austral summer. p CO2 sw was negatively correlated with total phytoplankton and diatom abundances, as estimated from pigment signatures, in the zone south of the Antarctic Circumpolar Current; however, p CO2 sw was not correlated with haptophyte abundance. Additionally, a stronger correlation was found between p CO2 sw and total phytoplankton NPP than between chlorophyll a concentration and p CO2 sw . We reconstructed p CO2 sw at inter-annual scale using satellite data and assessed the inter-annual variability of air-sea CO2 flux. Over the period from 1997 to 2007, the integrated CO2 fluxes over the study region showed very large variations from a small source to a strong sink. Variations in the integrated CO2 fluxes were also correlated with changes in satellite-derived phytoplankton community in the Indian sector of the Southern Ocean and changes in the dominant phytoplankton community may control CO2 dynamics in the marginal ice zone. Highlights: We investigated relationships between sea surface p CO2 and phytoplankton community and net primary productivity. Sea surface  p CO2  was negatively correlated with diatom abundance, but not correlated with haptophyte abundance. Stronger correlation was found between sea surface p CO2 and net primary productivity, rather than phytoplankton abundance. Changes in phytoplankton community composition may control CO2 dynamics in the Southern Ocean.